Design, construction and performance of the Monash pultruded glass fibre-reinforced polymer footbridge. (May 2023) - Caprani, Colin C.; Ngan, Jun Wei; Ahmadi, Ehsan; Zhang, Shao Hua; Bai, Yu; Satasivam, Sindu
Abstract: This paper describes the design, construction, and performance testing of the Monash Bridge (MB). The MB is a pultruded glass fibre-reinforced (pGFRP) footbridge built from individual standard pGFRP sections bonded using epoxy. The MB is designed to conform to current guidelines for GFRP footbridges in order to evaluate their performance. The design process of the MB is facilitated with numerical modelling techniques. This paper details the construction method of the MB, from which lessons that are learned may be relevant to other similar constructions. The construction process shows the potential of epoxy-bonding in practical construction of similar structures. This paper also reports on the performance of the MB, namely the static and dynamic performances. While the static performance is shown to be good, testing showed high levels of acceleration responses during walking trials, indicating that current vibration rules are not generally applicable for GFRP footbridges and that more advanced assessment of vibration serviceability should be conducted for new designs.